Passive physical barrier modulates UVB-induced METosis-related MPO expression and activity, 25-hydroxyvitamin D3-1alpha-hydroxylase, and the shift of tissue-resident macrophages toward M1-associated iNOS - Meterfi, Farah Sara; Zoudji, Souad; Bendjeffel, Nour Elhouda; Messali, Rabia; Boudjelal, Fadila; El Mezouar, Chahrazed; Brikci Nigassa, Nawal; Mekkaoui, Zineb; Brikhou, Slimane; Mennechet, Franck JD; Touil-Boukoffa, Chafia; Li, Xin; et al. (Frontiers in Immunology, 2025)
BackgroundThis study investigated the role of UVB radiation and the influence of a simulated passive barrier on the enzymatic conversion of 25-hydroxyvitamin D3 (25(OH)D3) by 1-alpha hydroxylase and its effects on the functional activity of tissue-resident macrophages.MethodsMurine peritoneal tissue-resident macrophages (PRMφs) were exposed to three conditions: (1) Baseline (Control group), with no light exposure; (2) UVB+/RF- group, exposed to UVB rays without passive barrier simulation; (3) UVB+/RF+ group, UVB exposure with a thin layer of rat fur to mimic the passive barrier on the skin.ResultsUVB exposure did not significantly alter 25OHD3 levels across groups but led to a marked downregulation of 1-alpha hydroxylase, particularly with the simulated barrier. UVB slightly enhanced phagocytosis and significantly increased nitric oxide (NO) and hydrogen peroxide (H2O2) production. Moreover, hypochlorous acid (HOCl) levels were significantly upregulated in the UVB-exposed PRMφ group, whereas they returned to baseline levels in the UVB+/RF+ group. Furthermore, both MPO expression and activity were markedly upregulated after UVB exposure and downregulated in UVB+/RF+ group, suggesting that the overall effect of UVB on METosis-related MPO activity was substantially attenuated by the simulated barrier (for both comparisons, p < 0.001 by ANOVA test). Additionally, UVB exposure shifted PRMφs toward M1-phenotype, as evidenced by decreased ARG1 activity and increased iNOS activity and M1(iNOS)-to-M2(ARG1) ratio. Additionally, UVB downregulated catalase (CAT) activity and intracellular glucose (iGLU) levels, with a stronger effect in the barrier group. While UVB increased total cellular cholesterol content (tccCHOL), this effect was mitigated by the barrier. Finally, intracellular free calcium ion (ifCa2+) levels remained unaffected by UVB but showed a slight increase with the barrier.ConclusionsUVB exposure enhances tissue-resident macrophage function in a preclinical rat model, increasing respiratory burst, phagocytosis, and M1-like polarization. The simulated barrier modulates these effects, notably by reducing MPO expression and METosis-related activity, which suggests a potential attenuation of excessive inflammation. These findings provide valuable insights relevant to human immune modulation and support further translational research. Future studies should investigate the role of circadian rhythms and other cell types in UVB- and vitamin D-mediated immune modulation.